Evaluasi Pelatihan Otomotif Dalam Meningkatkan Keterampilan Peserta Didik Di UPT-BLK Palangka Raya - Wahidin Wahidin; Kusnida Indrajaya; Mardiana Mardiana; Santi Matondang; Giovani Sibarani (Jurnal Ilmiah Kanderang Tingang, 2022)
This study aims to evaluate automotive training in 2021, which will be carried out by UPT-BLK Palangka Raya. Especially those related to the process of implementing the training, the obstacles faced and how the results of the training relate to the graduation of the trainees. This study uses a qualitative approach with reference to Moleong's opinion, that qualitative research intends to understand the phenomena experienced by the research subjects, in this case direct observation of automotive training activities organized by UPT-BLK Palangka Raya in 2021. Data collection procedures with observations, interviews and documentation conducted by the researchers themselves. The analysis process was carried out from the beginning in the field and finished in the field by using Miles Hubermen model data analysis. The results of the research can be seen from planning, organizing, directing and controlling in training activities. Research planning starts from preparation for socialization, registration of participants, implementation of tests, graduation announcements, which are carried out online considering that it is still in the atmosphere of the COVID-19 pandemic. Furthermore, the instructor prepares curriculum and learning tools according to the provisions. The organization of automotive training is carried out using communication media by creating wash-up groups to facilitate communication. The briefing is carried out on the process of implementing face-to-face training by taking into account the health protocol. The control of this training is by direct monitoring from the leaders of the Palangka Raya UPT-BLK and from the leaders of the Samarenda region. Meanwhile, the obstacles faced during the training were that some of the training equipment was old, so new equipment was needed. Meanwhile, the results of the automotive training at UPT-BLK Palangka Raya in 2021 were quite good, reaching 80% of all participants.